EVALUASI DAN PENANGANAN GEOTEKNIK PADA JALAN LINGKAR BAWEN – AMBARAWA - Mohammad Bintang Kurniawan; Robi Nurwanto; Indrastono Dwi Atmanto; Bambang Pardoyo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Approximately along 800 meters to 1 kilometers of Bawen - Ambarawa ring road is alleged built on soft structure soil. One of the location in this condition is the site of bridge Tambakboyo construction, where the 11 meters connection way (oprit) of the bridge collapsed even though has used geotextile and cerucuk bamboo. And abutment structure of Tambakboyo bridge with pile foundation became tilt and was found cavities in the girder beam and head of abutment about 20 centimeters and soil degradation of bridges oprit about ± 3,25 meters. This Final Project contains about manual calculation of bearing capacity and soil degradation of Bridges oprit that happened in the location and also contains about the calculation using Plaxis program. The alternative solution using Plaxis program is to change the abutment structure from using pile foundation to bore pile foundation. From the Plaxis Program, for Pile foundation abutment structure is obtained total of displacement about 1.91 meters, pile pondation degradation about 0.07741 meters, oprit degradation about 0,88416 meters, and safety factor (SF) amounted 1.1084. And for Bore Pile Fondation abutment structure is obtained total of displacement about 0.71522 meters, pile pondation degradation about 0.00553 meters, oprit degradation about 0,88416 meters and safety factor (SF ) amounted 1.5668.